The role of circadian clock-controlled mitochondrial dynamics in diabetic cardiomyopathy - Jin, Zhenshuai; Ji, Yanwei; Su, Wating; Zhou, Lu; Wu, Xiaojing; Gao, Lei; Guo, Junfan; Liu, Yutong; Zhang, Yuefu; Wen, Xinyu; Xia, Zhong-Yuan; Xia, Zhengyuan; et al. (Frontiers in Immunology, 2023)
Diabetes mellitus is a metabolic disease with a high prevalence worldwide, and cardiovascular complications are the leading cause of mortality in patients with diabetes. Diabetic cardiomyopathy (DCM), which is prone to heart failure with preserved ejection fraction, is defined as a cardiac dysfunction without conventional cardiac risk factors such as coronary heart disease and hypertension. Mitochondria are the centers of energy metabolism that are very important for maintaining the function of the heart. They are highly dynamic in response to environmental changes through mitochondrial dynamics. The disruption of mitochondrial dynamics is closely related to the occurrence and development of DCM. Mitochondrial dynamics are controlled by circadian clock and show oscillation rhythm. This rhythm enables mitochondria to respond to changing energy demands in different environments, but it is disordered in diabetes. In this review, we summarize the significant role of circadian clock-controlled mitochondrial dynamics in the etiology of DCM and hope to play a certain enlightening role in the treatment of DCM.